Length-weight relationship and condition factor of hippocampus hippocampus and hippocampus guttulatus inhabiting eastern black sea - Başusta, Asiye; Özer, Ebru I.; Girgin, Hulya; Serdar, Osman; Başusta, Nuri (University of Punjab (new Campus), 2014)
In this study, length-weight relationships of two seahorse species were determined inhabiting Eastern Black Sea. Hippocampus hippocampus (38) and Hippocampus guttulatus (139) individuals were obtained by commercial fishermen in the Eastern Black Sea. Length-weight relationships of H. hippocampus were found as W=0.012TL2.41 (R2=0.90) and length-weight relationships of H. guttulatus were found as W=0.005TL2.84 (R 2=0.91) for all individuals. The type of growth for both sexes was negative allometric growth (b<3) for these species. Average condition factors of H. hippocampus and H. guttulatus have shown 0.38 and 0.41, respectively. Copyright 2014 Zoological Society of Pakistan.
Keywords: Condition factor; Eastern Black Sea; Hippocampus guttulatus; Hippocampus hippocampus; Length-weight relationship